Yaman ng bayan, bantayan! Understanding local public finance: basic guide for citizen's engagement. (Social Watch Philippines, 2014)
This module "Understanding Local Public Finance" is a written manifestation of an advocacy that aims to put people in the center of public finance ; where their interests are considered and taken into account, where their interests are considered and taken into account, where their needs are addressed, and, in due course, where they play an active role in the development path of their communities.